Phase transition, structure and color-transition behaviors of monocarboxylic diacetylene and polydiacetylene assemblies: The opposite effects of alkyl chain length - Chanita Khanantong (2019)
© 2018 Elsevier B.V. This contribution demonstrates the structural-property relationship of diacetylene(DA) and polydiacetylene(PDA) assemblies in solid state and aqueous suspension. We explore two series of 7 monocarboxylic DA monomers and the resulting PDAs, constituting systematic variation of alkyl chain length at the tail and carboxylic head group position. The shortening of DA alkyl tail causes a reduction of its melting temperature. The shortening of alkyl segment adjacent to the carboxylic head group, in contrary, causes the opposite effect. The DA monomer constituting the shortest alkyl segment exhibits the highest melting temperature. Infrared spectroscopy is utilized to probe the strength of local interactions within these DA assemblies. X-ray diffraction reveals the variation of segmental orientation within the lamella bilayer structure of these DAs and PDAs depending on the alkyl chain length. The change of alkyl length also affects morphology and particle size. The color-transition behaviors of these PDAs investigated upon exposure to heat, ethanol and NaOH show discrepancies. The thermochromic transition temperature of PDAs is consistent with the melting temperature of their DA precursors. Interestingly, perturbation of the systems by adding ethanol or NaOH results in rather different trends, attributed to different local interactions of these stimuli at the interfacial region.